2017
DOI: 10.18553/jmcp.2017.23.7.745
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Endometriosis Symptoms on Absenteeism and Presenteeism in the Workplace and at Home

Abstract: The design and financial support for this study was provided by AbbVie. AbbVie participated in data analysis, interpretation of data, review, and approval of the manuscript. Coyne and Gries are employees of Evidera- Evidence, Value & Access by PPD and were paid scientific consultants for AbbVie in connection with this study. Soliman, Castelli-Hayley, and Snabes are AbbVie employees and may own AbbVie stock or stock options. Surrey is affiliated with Colorado Center for Reproductive Medicine and was paid by Abb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 27 publications
10
124
0
3
Order By: Relevance
“…The fact that endometriosis has a negative impact on women's professional life is neither new, nor surprising [3,4,6]. A recent review of the literature [21] highlighted that the economic burden of endometriosis is associated with both direct costs (inpatient and outpatient costs, pharmacological treatments, and other healthcare services) and indirect costs due to decreased work productivity, sick leave and time off to attend medical appointments, or even loss of employment, although with great worldwide variations (see also [22][23][24][25]). Of the 12 studies included in this 2016 review by Soliman et al [21], only one [26] was conducted in Italy and reported drug regimen costs per patient per 6 months, while a 10-country study by Nnoaham et al [17] showed that Italian endometriosis patients reported the highest absenteeism-related costs (US$231/wk) and the second highest presenteeism costs (around US$230/wk) after the patients belonging to the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that endometriosis has a negative impact on women's professional life is neither new, nor surprising [3,4,6]. A recent review of the literature [21] highlighted that the economic burden of endometriosis is associated with both direct costs (inpatient and outpatient costs, pharmacological treatments, and other healthcare services) and indirect costs due to decreased work productivity, sick leave and time off to attend medical appointments, or even loss of employment, although with great worldwide variations (see also [22][23][24][25]). Of the 12 studies included in this 2016 review by Soliman et al [21], only one [26] was conducted in Italy and reported drug regimen costs per patient per 6 months, while a 10-country study by Nnoaham et al [17] showed that Italian endometriosis patients reported the highest absenteeism-related costs (US$231/wk) and the second highest presenteeism costs (around US$230/wk) after the patients belonging to the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors used standardized tools to measure workrelated variables: Work Productivity and Activity Impairment Questionnaire [16,24,25], a short version of Work Ability Index [8], Global Study of Women's Health Questionnaire [24], work-related module of the Endometriosis Health Profile [8] or Health-Related Productivity Questionnaire [23]. Two teams of researchers developed their own surveys [9,16].…”
Section: Methodsmentioning
confidence: 99%
“…In the reviewed studies, women were identified in patients' registers and invited to the study by post or e-mail [8,10,16,22,23] or they were recruited from hospital wards [9,24,25].…”
Section: Characteristics Of Selected Studies Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations